2014
DOI: 10.1155/2014/592719
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Investment, Foreign Direct Investment, and Economic Growth Nexus: A Case of Pakistan

Abstract: This study aims to find dynamic interaction between domestic investment, foreign direct investment, and economic growth in Pakistan for the period 1976-2010. Phillips and Perron (PP) test is used to assess unit root in the concerned data series. Johansen cointegration approach applied to examine the long run relationship and Toda-Yamamoto causality approach is exercised to evaluate causal linkages. Besides foreign direct investment inflow to Pakistan and domestic investments variables, this study also used GDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 14 publications
6
42
0
1
Order By: Relevance
“…Many studies revealed the role of FDIs in the economic growth in the developing or less-developed countries, through technological spillovers in the host economy. Ullah, Shah, and Ullah Khan (2014) and Ghazali (2010) found similar results in Pakistan and bidirectional causality has been found between FDIs and domestic investments. A unidirectional causality is found between FDIs and economic growth and all these findings show that FDIs supports both domestic investment and economic growth in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 70%
“…Many studies revealed the role of FDIs in the economic growth in the developing or less-developed countries, through technological spillovers in the host economy. Ullah, Shah, and Ullah Khan (2014) and Ghazali (2010) found similar results in Pakistan and bidirectional causality has been found between FDIs and domestic investments. A unidirectional causality is found between FDIs and economic growth and all these findings show that FDIs supports both domestic investment and economic growth in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 70%
“…Saaed and Hussain (2015), Zeren and Ari (2013), Hatemi-J and Irandoust (2000), Yücel (2009) and Kar et al (2014) investigate the causal effects between trade openness and economic growth and the findings show that trade openness have a positive and significant effect on growth. Ullah et al (2014) investigated the relationship between domestic investment, foreign direct investment, and economic growth in Pakistan for the period 1976-2010. The findings pinpointed the existence of a long run relationship between foreign direct investment and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, there have been inflows of Foreign Direct Investment (FDI) and increase in the level of domestic investment in developing economies. The foreign direct investment inflows to developing countries have also increased during the last four decades (Ullah, Shah & Khan, 2014). But recently, statistics have shown that FDI inflows to Africa declined from US $50.4 billion in 2016 to US $42 billion in 2017 (a 21% drop) (UNCTAD, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Oyedokun and Ajose (2018), Lautier and Moreaub (2012), Alfa and Garba (2012) and Bakari (2017), among others have investigated whether domestic investment can significantly attract foreign investment in developing countries. Some scholars have investigated the interactions between foreign investment, domestic investment and economic growth in individual developing countries (Ullah, Shah & Khan, 2014;Lautier & Moreaub, 2012;Kukaj & Ahmeti, 2016). Other scholars have also examined the effect of foreign direct investment on economic growth of developing and developed countries using panel data (Alvarado, Iñiguez & Ponce, 2017;Iamsiraroj, 2016;Agbloyor, Gyeke-Dako, Kuipo & Abor, 2016;Adams & Opoku, 2015;Gui-Diby, 2014;Ndikumana & Verick, 2008;Sukar, Ahmed & Hassan, 2007).…”
Section: Introductionmentioning
confidence: 99%